Open Questions with Collective Rights of the Employees in Light of Current Amendments in Labour Legislation - Jovanović, Predrag (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Current amendments of the 2014 labour legislation did not bring qualitative changes in the sphere of collective rights of the employees, that is, for the reasons of trade union freedom and rights, collective bragaining and participation of the employees in decision-making. There were grounds for this based on international labour conventions, both the ones that have been ratified and the ones that haven’t been ratified but which offer right ways for the change in the sphere of of the said rights. This especially goes for the sphere of collective bargaining, which today remains with many questions open which result in the fact that such bargaining is in terrible crisis, i.e, collective employment contracts are more and more being left out of the legal system, as the most important autonomous acts of regulation of labour relations. This paper offers possisble solutions also for overcoming the said crises.